2008
DOI: 10.1007/s10532-008-9234-y
|View full text |Cite
|
Sign up to set email alerts
|

Degradation pathway of an anthraquinone dye catalyzed by a unique peroxidase DyP from Thanatephorus cucumeris Dec 1

Abstract: The reactants produced by action of a purified unique dye-decolorizing peroxidase, DyP, on a commercial anthraquinone dye, Reactive Blue 5, were investigated using electrospray ionization mass spectrometry (ESI-MS), thin-layer chromatography (TLC), and (1)H- and (13)C- nuclear magnetic resonance (NMR). The results of ESI-MS analysis showed that phthalic acid, a Product 2 (molecular weight 472.5), and a Product 3 (molecular weight 301.5), were produced. Product 2 and Product 3 were generated by usual peroxidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 30 publications
1
62
0
Order By: Relevance
“…In addition, the enzyme showed higher decolorization activity toward RB5, RB4, Acid Blue 45, and the triazine dyes Procion Blue H-ERD and Procion Blue H-EXL, with Ͼ70% decolorization within 2 h. Decolorization of RB5 and Acid Blue 45 by AnaPX resulted in a decrease in absorbance at 600 nm and an increase in absorbances at 400 to 500 nm accompanied with formation of a reddish-brown product with an azo link (2,2-disulfonyl azobenzene). These findings are consistent with those reported for the DyP1 isozyme (31). Interestingly, the formation of reddish-brown product was not observed in the vinyl sulfonate AQ dyes (RB19, RB114, and RB4), indicating that AnaPX uses different degradative pathways for these dyes and for RB5 and Acid Blue 45.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, the enzyme showed higher decolorization activity toward RB5, RB4, Acid Blue 45, and the triazine dyes Procion Blue H-ERD and Procion Blue H-EXL, with Ͼ70% decolorization within 2 h. Decolorization of RB5 and Acid Blue 45 by AnaPX resulted in a decrease in absorbance at 600 nm and an increase in absorbances at 400 to 500 nm accompanied with formation of a reddish-brown product with an azo link (2,2-disulfonyl azobenzene). These findings are consistent with those reported for the DyP1 isozyme (31). Interestingly, the formation of reddish-brown product was not observed in the vinyl sulfonate AQ dyes (RB19, RB114, and RB4), indicating that AnaPX uses different degradative pathways for these dyes and for RB5 and Acid Blue 45.…”
Section: Discussionsupporting
confidence: 91%
“…The ability of these proteins to effectively degrade hydroxyl-free AQ and azo dyes as well as the specificity for typical peroxidase substrates illustrates their potential use in the bioremediation of wastewater contaminated with synthetic dyes. However, with the exception of a DyP from the plant pathogenic fungus T. cucumeris Dec1 (an anamorph of Rhizoctonia solani, a very common fungal plant pathogen), which has been characterized extensively (18,28,(30)(31)(32)34), little information is available on other members of the DyP family. In particular, studies on bacterial DyPs have been limited to only the automatically translated sequence or structural data (41,42).…”
mentioning
confidence: 99%
“…The mechanism of DyPs is proposed to be similar to that of plant peroxidases (17,18). Generally, the catalytic cycle of aplant peroxidase includes the resting state and transient intermediates that consist of compound I and compound II.…”
mentioning
confidence: 99%
“…In addition to typical peroxidase activity, a hydrolase or oxygenase activity has been suggested for DyP (20). The physiological role of DyPs is still controversial, but it has been suggested that they are part of the catalytic system secreted by fungi for the oxidation of nonphenolic substrates, such as lignin and/or toxic aromatic products, or as a defense mechanism against oxidative stress (21).…”
mentioning
confidence: 99%